Réponses

  • Omnes
  • Modérateur confirmé
2014-02-17T22:39:22+01:00
Salut,

1/

(3x+3)² = 9/16
(3x+3)² - 9/16 = 0
(3x+3)² - (3/4)² = 0
(3x + 3 - 3/4)(3x+3+3/4) = 0
(3x + 9/4)(3x + 15/4) = 0

3x + 9/4 = 0
3x = -9/4
x = (-9/4)/3
x = -3/4

3x + 15/4 = 0
3x = -15/4
x = (-15/4)/3
x = -5/4


2/
9x²+30x+25=0
(3x)² + 2*5*3x + 5² = 0
(3x+5)² = 0
3x + 5 = 0
3x = -5
x = -5/3

3/

3:2x²+x=0
x(3/2x + 1) = 0
x = 0
3/2x +1=0
3/2x = -1
x = -1/(3/2)
x = -2/3

4/

4x+1-(4x+1)(6x+5)=0
1*(4x+1) - (4x+1)(6x+5) = 0
(4x+1)[-(6x+5) + 1] = 0
(4x+1)(-6x-5+1) = 0
(4x+1)(-6x -4) = 0
-2(4x+1)(3x + 2) = 0

4x + 1 = 0

4x = -1
x = -1/4

3x + 2 = 0
3x = -2
x = -2/3

Bonne soirée !



Le commentaire a été supprimé
MERCI a TOUS CEUX QUI MON REPONDUE ET AIDER MERCI BCP
2014-02-17T22:58:44+01:00
1_ (3x+3)² =9/16------------------- (3x+3)² -(3/4)² =0
(3x+3+3/4)( 3x+3-3/4)=0
3x=3/4-3 ou 3x =-3-3/4
       3-12                    -12-3
3x=------------- ou 3x = --------------------
           4                          4
         -9                  -15
x=------------  ou x =-------------
       12                    12
x=-3/4 ou x= -5/4

2))     9x² +30x+25 =0
 ( 3x+5)² =0  cad 3x+5 =0 cad x =-5/3.